Pengaruh Status Gizi Ibu Nifas terhadap Penyembuhan Luka Post Partum Operasi Sectio Caesaria - Maesaroh Maesaroh; Sylvia Meristika Rachman (Jurnal Kesehatan Pertiwi, 2019)
Tindakan persalinan dengan sectio caesaria ternyata juga belum menjamin keselamatan ibu seutuhnya, karena luka bekas jahitan sectio caesaria juga bisa mengalami infeksi. Penelitian ini bertujuan untuk mengetahui pengaruh status gizi ibu nifas terhadap penyembuhan luka post partum operasi sectio caesaria di RSU Permata Bunda Ciamis tahun 2018. Hasil penelitian yang telah didapat adalah status gizi ibu nifas yang telah dilakukan operasi sectio caesaria di RSU Permata Bunda Ciamis tahun 2018 adalah 33,3% kurus, 40,0% normal dan 26,7% gemuk. Penyembuhan luka post partum operasio sectio caesaria di RSU Permata Bunda Ciamis tahun 2018 adalah 66,7% normal dan 33,3% ada gangguan. Ada pengaruh signifikan status gizi ibu nifas terhadap penyembuhan luka post partum operasio sectio caesaria di RSU Permata Bunda Ciamis tahun 2018 dengan p-value 0,038. Ibu post partum diharapkan dapat lebih meningkatkan kualitas pengetahuan tentang penyembuhan luka post sectio caesarea. Kata Kunci : Status Gizi, Penyembuhan Luka, Sectio Caesaria The act of childbirth with a sectio caesaria apparently also does not guarantee the safety of the whole mother, because the sores of the cesarean section can also become infected. This study aims to determine the effect of postnatal maternal nutritional status on post partum cesarean section wound healing in Permata Bunda Ciamis General Hospital in 2018. The results of the research that have been obtained are the nutritional status of postpartum mothers who have undergone caesarean section surgery at Permata Bunda Ciamis General Hospital in 2018. 33.3% were thin, 40.0% were normal and 26.7% were obese. Healing of post partum surgical section of caesarean section at Permata Bunda Ciamis General Hospital in 2018 was 66.7% normal and 33.3% was impaired. There is a significant influence on the nutritional status of postpartum mothers in healing post partum operative caesaria wounds at Permata Bunda Ciamis General Hospital in 2018 with a p-value of 0.038. Post partum mothers are expected to further improve the quality of knowledge about post sectio caesarean wound healing. Keywords: Nutrition Status, Wound Healing, Sectio Caesaria